Self-efficacy as a key psychological predictor of learning independence among students in an integrated Islamic elementary school - Susantie Susantie; Lucia Rini Sugiarti; Erwin Erlangga (Cendikia : Media Jurnal Ilmiah Pendidikan, 2026)
As the foundation for lifelong learning, independent learning is an important psychological skill that must be developed from elementary school. The internal component of self-efficacy is crucial for enhancing independent learning. The purpose of this study was to investigate how self-efficacy influences elementary school students' ability to learn independently. A total of 87 fifth-grade students selected from the overall sample were included in a quantitative correlational design. Validated measures of independent learning and self-efficacy were used to collect data. Independent learning and self-efficacy were found to be significantly positively correlated based on Pearson correlation analysis (r = 0.523, p < 0.01). Simple linear regression analysis showed that self-efficacy explained 27.4% of the variation in independent learning (R2 = 0.274). These findings indicate that students with higher self-efficacy tend to demonstrate greater ability to manage and regulate their learning independently. The study highlights the importance of strengthening self-efficacy as a psychological foundation for promoting learning independence from an early educational stage